Implementation of Clean and Healthy Living Behavior (PHBS) in Kindergarten - Mahfudzo, Siti; Sitorus, Ahmad Syukri (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
The implementation of Clean and Healthy Living Behavior (PHBS) in early childhood education environments plays a strategic role in shaping healthy habits from an early age. This study aims to describe the implementation of PHBS at Al-Ikhwan Kindergarten, analyze the role of teachers and the surrounding environment, and identify the factors that influence its success. A descriptive qualitative approach was used, with data collected through in-depth interviews and direct observation. The findings show that PHBS has been implemented through habits such as personal hygiene, environmental cleanliness, healthy eating patterns, and light physical activities. Educators play a central role in fostering these habits by integrating health values into fun and participatory teaching methods. Additionally, support from parents, school policies, and adequate facilities serve as key factors in creating a conducive environment for establishing healthy behavior. Therefore, the implementation of PHBS from an early age requires not only active and creative teachers but also the involvement of all stakeholders in building a sustainable culture of healthy living.